The Nature of Sleep in the Qur'an - Muti’ah, Khansa Shohabiyatul; Rokhani, Siti; Murdianto, Murdianto (STIT Sunan Giri Bima, 2025)
Sleep is a natural human phenomenon that plays an important role in maintaining physical and psychological balance. The Qur'an discusses sleep in several verses (including QS. Al-An'am: 60, Az-Zumar: 42, Al-Furqan: 47, and Ar-Rum: 23), describing it as a divine system (sunnatullah) and a manifestation of Allah's mercy, not merely a biological need. This study aims to examine the essence of sleep from the perspective of the Qur'an based on M. Quraish Shihab's Tafsir Al-Mishbah and analyze its relevance to contemporary health psychology. The research uses a qualitative method with a thematic (maudhu‘i) approach, through the collection of Qur’anic verses related to sleep, analysis of their semantic structure and context, and their relationship with psychological theories about rest, stress regulation, and emotional recovery. The results show that Tafsir Al-Mishbah interprets sleep as a sign of Allah's power and human dependence, representing a temporary withdrawal of consciousness or “little death” (al-mawt al-sughra). Sleep also functions as a means of spiritual renewal that brings tranquility (sukūn) and psychological recovery. These findings are consistent with the views of health psychology and neuroscience regarding the restorative role of sleep. This study confirms the Qur'an's view of physical and spiritual harmony and offers an interdisciplinary framework that connects Qur'anic interpretation with modern mental health discourse.